Analisis Pencemaran Air Sungai Denai akibat Pembuangan Limbah Perternakan Babi di Lingkungan Jermal Baru - Yemima Meslina Elisabet Hutajulu; Ranti Asnita; Hartono Hartono; Marlinang Isabella Silalahi; Putri Yunita Pane (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
River pollution can occur due to the influence of waste that exceeds the predetermined quality standards, besides that it is also determined by the discharge of waste water produced, if the river water discharge is large, the concentration of waste will be neutralized due to the dilution process. This study aims to determine the determinants of water pollution in the Denai River. This type of research is a descriptive study with a total sample of 31 respondents. Based on the results of the univariate test, it states that the level of knowledge and attitudes of the community is good, namely 27 people (87.1%) and 28 people (90.3%) , while community action is bad, namely 28 people (90.3%) and this results in The Denai River in the Jermal Baru Watershed is heavily polluted. Based on laboratory tests, the parameters of suspended solids and pH are not contaminated, while BOD, DO, Fecal coli and Total coliform have been contaminated and the level of water pollution in Denai River is at a heavily polluted level (score -90) obtained by the storet method contained in KepMenLH No. 115 of 2003. Suggestions from researchers are expected to people around River Water to be more concerned about and understand the risks of livestock waste being discharged directly into the river.Keywords: Biochemical oxygen demand, dissolved oxygen, pH, total coliform bacteria and Fecal coli.